Psychological Impact Of UIN Sunan Ampel Surabaya Students On Academic Arabic Language Mastery - Fuad Hasim, Muhamad; Akhmad Taufiq, Mirwan; Baihaqi, M; Amaliyah, Nurul; Rachmawati, Emilia (STIQ Amuntai, 2025)
This study aims to determine the psychological impact on Uinsa students in mastering academic Arabic. This study was conducted by interviewing 10 postgraduate students of the Arabic Language Education Study Program, semester 1, at the State Islamic University of Sunan Ampel, Surabaya. The research method used in this study is qualitative research, namely descriptive analysis. We selected the research subjects using the purposive sampling method. Data collection was carried out by interviewing research subjects using structured interviews and unstructured interviews. The research found that 1) 80% of respondents said learning Arabic on campus can affect their mental health. 20% of the respondents indicated that the process of mastering Arabic on campus does not influence their mentality.does not influence their mentality. 2) 100% of respondents believe that readiness to be serious is something that must be present in every student in the process of mastering Arabic. 3) 50% of respondents answered that difficulty in vocabulary or mufrodat is an obstacle in the process of mastering Arabic. Meanwhile, 20% of other respondents revealed difficulties in pronunciation style or lahjah. And the remaining 30% of respondents revealed a lack of mastery of Qowaid or Arabic grammar. 4) 80% of respondents answered that refreshing is the right way to stabilize emotions and mentality in every student. Meanwhile, 20% of the respondents stated that they maintain their emotional and mental stability by persistently learning and striving until they achieve their goals.